The Impacts of the Inwards and Outwards FDI on the Development Measured By HDI: the Case of United Arab Emirate - Akram Masoud Haddad (International Journal of Economics and Financial Issues, 2018)
Different studies conducted in past regarding the FDI policies in different countries and regions and its impacts on the recipient countries, most of these studies concentrated on the impact of FDI on the economic growth measured by the GDP. in this study the impact of both the inflow and outflow FDI on the economic growth measured by HDI which is the proxy for the health, income and education in the countries, United Arab Emirates is the case where there are both cases of the FDI flows are clear and big. Ordinary least square method is applied and both simple and multiple regressions is used, the results show that both inflow and outflow FDI have an impact on the HDI alone while considering both together only the inflow FDI has an impact on the HDI so that the impacts of the outflow is eliminated with the impact of the inflow FDI. The explanation of that is the inflow FDI brings with it many direct benefits to the people of the country while the outflow FDI brings indirect benefits to these people. However, country like United Arab Emirates should pay more attention for the both inflow and outflow investment so that the dependency on will be less. Keywords: human development index, investment, foreign direct investment, United Arab Emirates, economic growth. JEL Classifications: F21, F43, N15, O15, O47